A new frequency-domain TLM algorithm using a decoupled symmetrical condensed node - Jifu Huang; Vahldieck, R.; Hang Jin (1994 IEEE MTT-S International Microwave Symposium Digest (Cat. No.94CH3389-4), 1994)
This paper describes a new algorithm for the frequency-domain TLM (FDTLM) method. The conventional 12-port symmetrical condensed node (SCN) utilized in the past to construct the FDTLM algorithm is decoupled into a pair of independent 6-port nodes. Based upon the properties of decoupled nodes, a new decoupled algorithm for the entire FDTLM network is derived. As a result of this, the memory space requirements of the FDTLM is reduced significantly and the savings in CPU-time is more than 50 per cent.< >